A Two-layer Coupled Network Disease Transmission Model Considering Multiple Messages - Li, Yang; Sun, Gengxin; Bin, Sheng (International Journal of Computer Science and Information Technology, 2024)
In order to discuss the coupling dynamics relationship between disease propagation and information diffusion more accurately, we propose a SIR−UAOE1E2 information-disease two-layer coupling network propagation model, which takes into account individual heterogeneity and the mutual influence of nodes, introducing hesitant individuals. The impact of various behavioral factors of observing individuals on disease transmission under the influence of various information was explored through simulation experiments. The results show that enhancing the correctness of observing individual behavior decisions, improving their sensitivity to disease information, and enhancing their response intensity to infected neighbors, would play a positive role in suppressing disease outbreaks.